Resposta:
# -48-7sqrt (6) #
Explicació:
# 12-15sqrt (6) + 8sqrt (6) -10sqrt (36) #
# = 12-15sqrt (6) + 8sqrt (6) -10sqrt (6 ^ 2) #
# = 12-15sqrt (6) + 8sqrt (6) -10 * 6 #
# = 12-15sqrt (6) + 8sqrt (6) -60 #
# = 12-60 + (- 15 + 8) sqrt (6) #
# = - 48-7sqrt (6) #
Resposta:
# -48- (7 * sqrt (6)) #
Explicació:
# 12 + (- 15 * sqrt (6)) + (8 * sqrt (6)) + (- 10 * sqrt (36)) #
Ho sabem #sqrt (36) = 6 #.
Tan, # 12 + (- 15sqrt (6)) + (8 * sqrt (6)) + (- 60) #.
#12-60=-48#
Tan, # -48 + (- 15sqrt (6)) + (8 * sqrt (6)) #
Ara, traieu #sqrt (6) # dels últims dos parèntesis.
Això ens donaria # -48 + (sqrt (6) * (- 15 + 8)) #
#-15+8=-7#
Així doncs, la resposta seria # -48- (7 * sqrt (6)) #